Analysis of Coaching, Organizational Culture, and Performance Appraisal of Employee Productivity in High School: Literature Review - Primadi Candra Susanto; Juliater Simarmata; Wenny Desty Febrian; Ari Sulistyowati; Siti Annisa Wahdiniawati; Ryan Firdiansyah Suryawan (Dinasti International Journal of Education Management And Social Science, 2023)
The purpose of this study act as a guide or guideline for researchers in designing methodologies, collecting data, analyzing results, and interpreting findings and also provides clear direction and focus to researchers, thus ensuring that the study is relevant and useful. This research employs a qualitative research approach by the researcher. Qualitative methods are essentially exploratory research techniques used to investigate the causes, perspectives, and opinions to address research questions. The selection of this qualitative research approach is appropriate. Data collection for this research will be conducted from primary and secondary sources. The researcher collects primary data to address research questions through a review of scholarly works, journals, books, websites, and blogs used in this study. Effective coaching is key to improving employee skills, motivation, and performance. A purposeful and focused coaching program can help employees overcome challenges, develop potential, and achieve their goals more effectively. A positive and inclusive organizational culture creates a motivating, collaborative, and productive work environment. By promoting values such as trust, cooperation, and innovation, organizations can increase employee engagement and create a foundation for long-term success. Organizational culture, and performance appraisals, organizations can create a work environment that supports, motivates, and enables employees to reach their full potential. Keywords: Coaching, Organizational Culture, Performance, Employee Productivity